Factors influencing sustainable heritage tourism among local community of Taiping, Malaysia - Abdul Aziz, Mohd Mustafa (2019)
The main purpose of this study is to holistically understand the role of community participation and tourism resources in influencing the sustainable heritage tourism practice of the Taiping local community. Quantitative approach use in this study to gather data. Most of the respondents claimed that there was a strong indication of community participation in the village and this is evident from the turnout and response by the villagers when meetings are called for discussions on matters regarding the local administration and tourism development. The influence of the community resources and community development dimensions on attainment of sustainable heritage tourism was determined. Multiple regression analysis using stepwise method was employed to identify the predictors. Six independent variables were found to contribute significantly in clarifying the variations in tourism sustainability. The results showed that cultural resource and infrastructure resource variables were better determinants for economic sustainability dimension while human resource, infrastructure resource, nature resource, and capacity building variables were better determinants for sociocultural sustainability dimension. Apart from this, infrastructure resource and capacity building variables were better determinants for environmental sustainability dimension. Overall, cultural resource, financial resource, infrastructure resource, and capacity building variables were better determinants for overall sustainability dimension. Surprisingly, participation and empowerment were not found to have significant relationships to any economic, socio-cultural, and environment sustainability dimensions. This is most likely because of majority of the respondents were not involved in tourism and they were not empowered in tourism planning. The infrastructure development in Perak is still in infancy stage. Since Taiping is the second largest city in Perak, it is suggested that a public transport hub should be developed in Taiping so that it is easily accessed by tourists. Therefore, tourism stakeholders should work closely to promote Taiping as a heritage tourism destination.